When everything starts with an empty space. Eutopia (2022) by Trickster-p or the game of the Anthropocene (Itinera, 2023)
The essay reflects on the installation-performance Eutopia (2022), conceived and directed by the Swiss-Italian collective Trickster-p, i.e. by Cristina Galbiati and Ilija Luginbühl in collaboration with game designer Pietro Polsinelli, Zeno Gabaglio for the sound space and Studio CCRZ for the graphic design. Eutopia addresses the environmental crisis we are becoming aware of with significant delay in raising cultural and political awareness to counteract the ongoing process of individual and collective removal. The essay inquires the theoretical assumptions on which this installation- performance is based and how it conveys the important message that inspired its creators to investigate how the performing arts can contribute to imagining the future of our planet. As a board game of the Anthropocene, Eutopia transforms the performative space into a political space in which people exchange and discuss ideas and visions about the environment and how to care for it actively.